ANALISIS PENERAPAN STANDAR GROOMING ROOM ATTENDANT DI BEST WESTERN PREMIER PANBIL BATAM - Ade Putra Isnanda; Windy Della Sari (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2020)
This research is descriptive analysis research that aims to analyze the application of room attendant grooming standards at Best Western Premier Panbil Batam, which includes always giving a smile and greeting to guests who meet in corridors, rooms and in hotels, looking attractive, wearing complete uniforms, always wearing name tags. no beard, no mustache, no long hair, no body odor, always pay attention to trolley cleanliness. The data collection methods used were observation and questionnaires. The type of data used is quantitative and qualitiative, while the data sources used are primary and secondary. The method used is non-probability sampling, one of which is the accidental sampling method. While the data analysis technique uses descriptive analysis. From the results of the research conducted, it was found that 857 had implemented grooming room attendants enough at Best Western Premier Panbil Batam